2018
DOI: 10.1155/2018/1092716
|View full text |Cite
|
Sign up to set email alerts
|

Demand Sharing Inaccuracies in Supply Chains: A Simulation Study

Abstract: We investigate two main sources of information inaccuracies (i.e., errors and delays) in demand information sharing along the supply chain (SC). Firstly, we perform a systematic literature review on inaccuracy in demand information sharing and its impact on supply chain dynamics. Secondly, we model several SC settings using system dynamics and assess the impact of such information inaccuracies on SC performance. More specifically, we study the impact of four factors (i.e., demand error, demand delay, demand va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…IPMA results in Table 5 and Figure 2 show that demand information sharing has the highest latent variable index values (3.91) and low latent variable performance (54.824) on inventory efficiency. This finding aligns with previous studies that found the importance of demand information sharing for performance (Cannella et al, 2018;Khanjari et al, 2017). Firms that improve their demand information sharing will increase overall performance in the supply chain.…”
Section: Importance-performance Map Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…IPMA results in Table 5 and Figure 2 show that demand information sharing has the highest latent variable index values (3.91) and low latent variable performance (54.824) on inventory efficiency. This finding aligns with previous studies that found the importance of demand information sharing for performance (Cannella et al, 2018;Khanjari et al, 2017). Firms that improve their demand information sharing will increase overall performance in the supply chain.…”
Section: Importance-performance Map Analysissupporting
confidence: 91%
“…These information systems can provide well-timed information to survive in highly competitive environments (Fernandes et al, 2017). Several studies have pointed out the importance of improving demand information sharing (Cannella et al, 2018;Khanjari et al, 2017), which connect with inventory information sharing (Kim and Chai, 2017). We argued that the enhanced inventory information sharing on market demand would improve inventory information sharing practices.…”
Section: Hypotheses Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Prasoon, Agarwal, & Kumar [13] built a two-echelon supply chain structure using simulation to compare centralized and decentralized supply chains in order to minimize the cost. Cannella, Dominguez, Framinan, & Bruccoleri [14] studied a simulation model to analyze two main sources of information inaccuracies that are errors and delays in a supply chain. Their study focused on demand error, demand delay, demand variability and average lead times.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To achieve these two goals, we conduct a simulation study to analyze how Canadian food supply chains have been disrupted by the COVID-19 pandemic using lobster industry in Nova Scotia as an example. As demonstrated by Klibi and Martel [4] and Cannella et al [5], simulation models are effective for analyzing supply chains under uncertain conditions.…”
Section: Introductionmentioning
confidence: 99%